Sovereign Risk and Implication of Monetary Policy: Evidence from Panel Data - Parla Onuk (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This paper reopens the discussion on the main dynamics behind the sovereign debt crisis focusing on global monetary policy. A panel logit model was applied using data from twenty countries between 1975 and 2022. According to the model, an increase in the U.S. interest rate is one of the significant factors fueling the likelihood of debt distress in developing countries. With this finding, we emphasize the dependency of developing countries on external factors through the interest rate and the importance of external dynamics. Additionally, an increase in short-term debt to total reserves and the ratio of international reserves to imports strengthens the likelihood of debt distress. Another important factor is the possibility that countries may fall into debt distress due to high inflation and low growth. Although these two variables are considered internal dynamics of countries, there is a strong direct relationship between the performance of production and expenditure in periphery countries and foreign capital. In this context, various recommendations are presented in the conclusion section for reconsidering debt crises and implementing appropriate policies.